Portugal no PISA 2000 Condições de participação, resultados e perspectivas - Glória Ramalho (Universidade do Minho, 2002)
This text presents the outcomes of the Portuguese participation in the first survey of the Programme for International Student Assessment (PISA) which took place in 2000, in 32 countries, 28 of them members of OECD. The target population comprised 15 years old students who had to face written tasks concerning reading literacy, mathematical literacy and scientific literacy, being reading literacy the major assessment domain. In PISA, reading literacy was defined as the ability of each individual to understand, using and reflecting on written texts, in order to achieve ones goals, to develop ones knowledge and potential, and to actively participate in society. PISA outcomes allow the following conclusions: i) Portuguese students had a modest average performance; ii) there are differences among the profiles of the students in the high levels and those of the low levels of literacy; iii) there are also differences among the profiles of the families of these two groups; iv) Portuguese students performed better when the text is a narrative; on the contrary, their performance is poor when the texts to be read belong to the dramatic genre or are long informative ones; it is even poorer when interpretation required accurate identification and location of information in the text; v) there isnt a strong correlation between students results in Portuguese and PISA performance.